Best treatment options for occult breast cancer: A meta-analysis - Wang, Rong; Yang, Hong-xin; Chen, Jie; Huang, Jian-jun; Lv, Qing (Frontiers in Oncology, 2023)
Objective：Occult breast cancer (OBC) is a rare malignant breast tumor. Due to the rare cases and limited clinical experience, a huge therapeutic difference has existed all over the world and standardized treatments have yet been established. Methods：A meta-analysis was conducted using MEDLINE and EMBASE databases to identify the choice of OBC surgical procedures in all studies: (1) patients undergoing axillary lymph node dissection (ALND) or sentinel lymph node biopsy (SLNB) only; (2) patients undergoing ALND with radiotherapy (RT); (3) patients undergoing ALND with breast surgery (BS); (4) patients undergoing ALND with RT with BS or not; (5) patients undergoing observation or RT only were excluded. The primary endpoints were mortality rates, the second endpoints were distant metastasis and locoregional recurrence. Results：Among the 3476 patients, 493 (14.2%) undergoing ALND or SLNB only; 632 (18.2%) undergoing ALND with RT; 1483 (42.7%) undergoing ALND with breast surgery; 467 (13.4%) undergoing ALND with breast surgery or not; 401 (11.5%) undergoing observation or RT only. After comparing the multiple groups, After comparing the multiple groups, both group 1 and 3 has a higher mortality rates than group 4 (30.7% vs 18.6%, P < 0.0001; 25.1% vs 18.6%, p = 0.007), group 1 have a higher mortality rates than group 2 and 3 (30.7% vs. 14.7%, p < 0.00001; 30.7 vs 19.4%, p < 0.0001). Group (1+3) had a prognosis advantage over group 5 (21.4% vs 31.0%, P < 0.00001). There was both no significant difference in distant recurrence rates and locoregional rates between group (1+3) and group (2+4) (21.0% vs 9.7%, p = 0.06; 12.3% vs 6.5%, p = 0.26). Conclusions：Based on this meta-analysis, our study indicates breast surgeries including modified radical mastectomy and breast conserving surgery combined radiation therapy may appear as the optimal surgical approach in OBC patients. RT cannot prolong both the time of distant metastasis and the local recurrences.